Система керування багаторівневим інвертором сонячної електричної станції - Левицький, Сергій Михайлович (НТУ "ХПІ", 2015)
Розроблено закон керування та структуру мережевого багаторівневого інвертора сонячної електростанції, який дозволяє утримувати режим роботи сонячного модуля в області точки відбору максимальної потужності і збільшити продуктивність сонячного модуля. Запропоновано вдосконалену модель регулятора поздовжньої складової струму інвертора, яка враховує рівень споживання реактивної потужності з вузла мережі, поточну напругу мережі та напругу сонячного модуля і дозволяє оптимізувати роботу інвертора як зі сторони сонячного модуля, так і з боку мережі за напругою. Запропоновано вдосконалену модель регулятора поперечної складової струму інвертора, яка враховує відношення спожитої активної потужності з вузла мережі до поточної потужності сонячного модуля і дозволяє оптимізувати роботу інвертора за навантаженням та частотою. Розглянуто приклад реалізації системи керування інвертором із запропонованими моделями на базі високопродуктивного мікроконтролера.

Purpose. The development of control law for network multilevel invertor of solar power station and design device for control law realization. Methodology. At synthesis of control law theory of automatic control, power network engineering and circuit technique are considered. The control law for distributive control over the direct-axis and quadrature-axis currents of invertor after abc-dq transform of three phase current’s momentary value is used. Results. The improved model of regulator of direct-axis invertor’s current is developed and provides the voltage optimization of invertor’s operating both from solar module and from network by means of calculation the reactive power consumption from network, voltage on network and voltage on solar module. The improved model of regulator of quadrature-axis invertor’s current is developed and provides the power and frequency optimization of invertor’s operating by means of calculation ratio of active powerconsumption and power from solar module. Originality. The offered control law and device, which realize it, is working out on secondary loop from power network smart grid with active and reactive power consumption monitoring. That provides the optimal operation of solar station both from solar module and from power network. Practical value. The proposed control law and structure of the network multilevel invertor for solar power station provide the operate mode of solar module in maximum power point and increasing the solar module’s productivity.
Control system for multilevel invertor of solar power station
Keywords: модуль сонячний; контролер; напруга; invertor; control; solar module